Large mid-esophageal granular cell tumor: benign versus malignant - Prarthana Roselil Christopher; Pamela Alice Kingsley; Harinder Singh Bedi; Kanwardeep Singh Kwatra; Shubra Rathore; Kanhu Charan Das (Rare Tumors, 2015)
Granular cell tumors are rare soft tissue neoplasms, among which only 2% are malignant, arising from nervous tissue. Here we present a case of a large esophageal granular cell tumor with benign histopathological features which metastasized to the liver, but showing on positron emission tomography-computerized tomography standardized uptake value suggestive of a benign lesion.